Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Review - Page 474: 34



Work Step by Step

$x^{2}$+12x+36=$x^{2}$+6x+6x+36=x(x+6)+6(x+6)= (x+6)(x+6)=$(x+6)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.